Comparing traditional conceptual modeling with ontology-driven conceptual modeling: An empirical study. (March 2019) - Verdonck, Michaël; Gailly, Frederik; Pergl, Robert; Guizzardi, Giancarlo; Martins, Beatriz; Pastor, Oscar
Abstract: This paper conducts an empirical study that explores the differences between adopting a traditional conceptual modeling (TCM) technique and an ontology-driven conceptual modeling (ODCM) technique with the objective to understand and identify in which modeling situations an ODCM technique can prove beneficial compared to a TCM technique. More specifically, we asked ourselves if there exist any meaningful differences in the resulting conceptual model and the effort spent to create such model between novice modelers trained in an ontology-driven conceptual modeling technique and novice modelers trained in a traditional conceptual modeling technique. To answer this question, we discuss previous empirical research efforts and distill these efforts into two hypotheses. Next, these hypotheses are tested in a rigorously developed experiment, where a total of 100 students from two different Universities participated. The findings of our empirical study confirm that there do exist meaningful differences between adopting the two techniques. We observed that novice modelers applying the ODCM technique arrived at higher quality models compared to novice modelers applying the TCM technique. More specifically, the results of the empirical study demonstrated that it is advantageous to apply an ODCM technique over an TCM when having to model the more challenging and advanced facets of a certain domain or scenario. Moreover, we also did not find any significant difference in effort between applying these two techniques. Finally, we specified our results in three findings that aim to clarify the obtained results. Highlights: Empirical study on adopting a traditional conceptual modeling technique and an ontology-driven conceptual modeling technique. Measure the difference in model quality and the effort required to create such a model. Understand and identify in which modeling situations an ODCM technique can prove beneficial compared to a TCM technique.